ANALISIS PENERAPAN DAN USULAN PERBAIKAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA PADA BAGIAN AUTOMOTIVE COMPONENT PT DPM - Silda, Mario; Hartono, Gunawarman; Herman, Robertus Tang (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Accidents often occur in the company. In order to prevent accidents, the company must consider the Occupational Health and Safety (K3) of its employees. This study discussed about K3, especially the calculation and analysis of the value of the Frequency Rate (FR), Severity Rate (SR), and Medical Treatment Injury Frequency Rate (MTIFR) Company from 2009 to downy mildew in June of 2010. The values of FR, SR, and MTIFR obtained varied because of differences in the number of accidents and total working hours of existing employees. After that, an analysis is conducted on the causes of these accidents. Direct cause of the accident consisted of 2 reasons, namely unsafe act and unsafe condition. Basic causes of accidents were 2 factors, namely individual factors and work factors. Individual factors that cause the highest accidents are due to employee motivation blunders and job factors are the highest cause of work accidents are due to poor design of equipment and workplaces.